2015
DOI: 10.1249/mss.0000000000000531
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ovarian Hormones on Strength Loss in Healthy and Dystrophic Female Mice

Abstract: Purpose The primary objective of this study was to determine if strength loss and recovery following eccentric contractions is impaired in healthy and dystrophic female mice with low levels of ovarian hormones. Methods Female C57BL/6 (wildtype) or mdx mice were randomly assigned to ovarian-intact (Sham) and ovariectomized (Ovx) groups. Anterior crural muscles were tested for susceptibility to injury from 150 or 50 eccentric contractions in wildtype and mdx mice, respectively. An additional experiment challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 40 publications
3
14
0
Order By: Relevance
“…This exercise protocol is recommended for pre-clinical studies (Treat-NMD, DMD_M.2.1.001). However, we found that muscle weakness and fragility were not exacerbated in the Run mdx as compared to Sed mdx mice, confirming a previous study [28]. These results indicate that the use of a more severe murine Duchenne muscular dystrophy model than the exercised mdx mice would be more useful in pre-clinical studies.…”
Section: Discussionsupporting
confidence: 89%
“…This exercise protocol is recommended for pre-clinical studies (Treat-NMD, DMD_M.2.1.001). However, we found that muscle weakness and fragility were not exacerbated in the Run mdx as compared to Sed mdx mice, confirming a previous study [28]. These results indicate that the use of a more severe murine Duchenne muscular dystrophy model than the exercised mdx mice would be more useful in pre-clinical studies.…”
Section: Discussionsupporting
confidence: 89%
“…Serum estradiol concentration declines dramatically at the average age of 51 in women, corresponding to the time of menopause (Baber et al, 2016). Estradiol deficiency reduces skeletal muscle mass and force generation in women (Greising et al, 2009; Phillips et al, 1993, 1996; Qaisar et al, 2013; Taaffe et al, 2005) and female rodents (Greising et al, 2011; Moran et al, 2007) and prevents the recovery of strength following contraction-induced muscle injury (Kosir et al, 2015; Rader and Faulkner, 2006) and traumatic muscle injury in female mice (Le et al, 2018). However, evidence that this regenerative phenotype involves effects of estradiol directly on satellite cells is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Serum estradiol concentration declines dramatically at the average age of 51 in women, corresponding to the time of menopause (Baber et al, 2016). Estradiol deficiency reduces skeletal muscle mass and force generation in women (Greising et al, 2009;Phillips et al, 1993;Phillips et al, 1996;Qaisar et al, 2013;Taaffe et al, 2005) and female rodents (Greising et al, 2011;Le et al, 2017;Moran et al, 2007) and prevents full recovery of strength following contraction-induced injury (Kosir et al, 2015;Rader and Faulkner, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, it has been hypothesized that the regulation of muscle inflammation (Le et al, 2015;McClung et al, 2007;Tiidus et al, 2001) and protein synthesis (Kamanga-Sollo et al, 2010;Kosir et al, 2015;McClung et al, 2007;McClung et al, 2006) is perturbed by estradiol deficiency and may contribute to impaired recovery . Previous work has also indicated that exercise-induced activation of satellite cells is less effective in the absence of estradiol , and that androgens contribute to the regulation of juvenile satellite cells during growth (Kim et al, 2016), but it has yet to be determined if there are cell autonomous mechanisms which involve estradiol acting directly on satellite cells .…”
Section: Introductionmentioning
confidence: 99%